PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI, INFORMASI, DAN KOMUNIKASI PADA MATERI KEMAGNETAN - Dewi Setiawati; Nengah Maharta; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2013)
This developmental research was intended to make an interactive instructional media of magnetism based on information and communication technology (ICT) that has an interesting quality, easy to use, very useful and effective. Media contains learning materials, animation, simulation, sound, video, exercises and competency tests. Development procedures are used to modify the design of instructional media development by Sadiman, et al. With the stages of work procedure that comprise needs analysis, setting objectives, subject materials, making a synopsis, script initial, prototype production, evaluation by material expert test dan the design expert test, revision, final script, product trials, and the final program. The result of one on one test and field test have proved media has an very interesting quality, very easy to use, and very useful for students. Field test data shows the students achievement of minimum completeness criteria for post-test results as much as 91.30% of the total students so that the product is effective to be used as an instructional media. Keywords: research and development, interactive instructional media, magnetism